Design of a Web-Based Credit Score Assessment System (Case Study: STMIK TIME) Using the Rapid Application Development Method - Gustaf Sunario, Herbert; Robet; Hendrik, Jackri (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
Higher education institutions have an important responsibility to provide quality educational services in order to achieve student satisfaction. However, various challenges are still encountered, particularly in academic administrative services and the availability of facilities and infrastructure. As visionary institutions, universities are required to continuously innovate and adopt leadership strategies that are adaptive to global changes and local challenges. STMIK TIME, as one of the higher education institutions in the field of information technology, has study programs that require an objective and structured lecturer performance assessment system. Lecturers, as professional educators, are expected to demonstrate optimal performance influenced by motivation, competence, leadership, and work environment. In the context of academic rank promotion, credit score assessment (PAK) must be carried out consistently in accordance with established procedures. Based on this background, this study aims to design a web-based lecturer credit score assessment system at STMIK TIME using the Rapid Application Development (RAD) method in order to accelerate the assessment process and improve academic administrative efficiency.